Use of Computer Graphics in the Educational Process, Project Training According to Construction Drawings - Omonov, D. E.; Otayorova, F. (European Journal of Life Safety and Stability (2660-9630), 2022)
From the first days after gaining independence, Uzbekistan began to realize the noble goal of establishing a free democratic state and ensuring a morally rich and dignified life of the people. The path of development that we have chosen is aimed at the renewal and development of the state and society, taking into account world experiences, as well as age-old national traditions, customs, and traditional lifestyle. During the 30 years of independence, there have been positive changes in almost all aspects of social, cultural and international life in the country. Active and effective steps have been taken regarding the integration of Uzbekistan into the world community, which is largely related to the level of creating opportunities for citizens of the country to freely access information.